UNEQUAL DISTRIBUTION OF JOINT ASSETS DUE TO DIVORCE - Sujoko, Ajik; Kauffman, James M. (EQUALEGUM International Law Journal, 2023)
Background. Joint assets are assets acquired by a husband and wife together during the period of marriage. Marriage Law Number 1 of 1974 does not regulate the division of joint assets, as a result, difficulties arise for legal administrators in resolving cases related to joint assets. This study aimed to describe the unequal distribution of joint assets due to divorce. Research Method. This research is considered as a field research or case study. It uses used descriptive analysis method and the type of research is qualitative research. The data collection procedures of this study were observation, interviews, and documentation. The case study of Semarang Religious Court Decision 512/Pdt.S/2023/PA.Sm. Findings. Joint assets are divided after divorce if the wife is more dominant in terms of looking for property through the Semarang Religious Court decision taken with a percentage of 1/3 for the husband and 2/3 for the wife, this is based on the judgment of the judge who thought that the wife should be the husband's responsibility, the wife was the one who worked hard to collect property, while the husband, who should have been more intensive in meeting household needs, turned out to be passive and only enjoyed the results of his wife's hard work. Conclusion. Marriage Law Number 1 of 1974 regarding the division of joint property adhering to the compilation of Islamic law articles 96 and 97 of the provisions mentioned above, where article 97 determines whether a divorced widow or widower lives each is entitled to half.